Development of mobile augmented reality-based geometry learning games to facilitate spatial reasoning - Mandala, Arif Sapta; Anwar, Lathiful; Sa'dijah, Cholis; Zulnaidi, Hutkemri (Jurnal Infinity, 2025)
Geometry learning requires a comprehensive understanding of spatial reasoning, but students face difficulty in mastering the skill. As a virtual technology, Augmented Reality (AR) offers a solution to overcome the challenges in spatial reasoning with the potential to represent and manipulate objects and develop spatial images mentally. Therefore, this research aimed to develop a mobile educational game named GEMBI AR to support students' spatial reasoning skills in geometry learning. The ADDIE model consists of analysis, design, development, implementation, and evaluation phases used to conduct research and development (R&D). The participants included six expert validators, two mathematics teachers, and eighteen eighth graders. In addition, the expert validators validated GEMBI AR in terms of quality. The result showed that GEMBI AR was valid as a geometry learning tool. According to the feedback of teachers and students, GEMBI AR was practical for educational purposes since the application positively impacted spatial reasoning. Students' spatial reasoning skills were also enhanced to compare the differences in the pre-test and post-test using Wilcoxon (Z = –3.578, p = 0.000 < 0.05). Meanwhile, the N-Gain score of 0.576, showing moderate improvement, reflected gains in spatial perception, mental rotation, and visualization. These findings suggest that GEMBI AR is a functional and valid educational resource useful for helping students develop geometric spatial reasoning. Thus, geometry learning supported by GEMBI AR has the potential to enhance spatial reasoning in secondary school.